Cardiac, Energy and Hormonal Blood Markers, and Lactatemia in Cows with Displaced Abomasum - Ribeiro, Ana Clara Sarzedas; Soares, Gliére Silmara Leite; Coutinho, Luiz Teles; Cajueiro, Jobson Filipe de Paula; Souto, Rodolfo José Cavalcanti; Silva, Bruna Higino de Souza; Soares, Pierre Castro; de Mendonça, Carla Lopes; Afonso, José Augusto Bastos (Acta Scientiae Veterinariae, 2020)
Background: Displaced abomasum (DA) is a common and economically important disorder that affects dairy cattle. Nutritional factors and adaptive responses that occur in the peripartum play a central role in the pathogenesis. The measurement of blood metabolites represents a useful tool for monitoring and prognostic determination in affected animals. Therefore, the objective was to evaluate cardiac, energy and hormonal blood markers, lactatemia, and insulin sensitivity in cows diagnosed with right displaced abomasum (RDA) and left displaced abomasum (LDA), comparing them with each other. Materials, Methods & Results: Nineteen cases of abomasum displacement in cows were studied, including 9 cases of RDA and 10 cases of LDA. The diagnosis was established by means of physical examination and measurement of the concentration of chlorides in the ruminal fluid (> 30mEq/L). After diagnosis, clinical-surgical therapeutic management was instituted. At the time of diagnosis (M1) and at the resolution of the case (M2), blood samples were collected to assess the variables: non-esterified fatty acids (NEFA), beta hydroxybutyrate (βHB), L-lactate, creatine kinase (CK), creatine kinase MB (CK-MB), cardiac troponin I (cTnI), lactate dehydrogenase (LDH), glucose, insulin, and cortisol. In addition, insulin sensitivity was estimated using the Revised Quantitative Insulin Sensitivity Check Index (RQUICKI) and RQUICKI-βHB. The means of the variables were compared, separating the effects of groups (RDA and LDA) and moments (M1 and M2), at the level of 5% probability. The concentrations of NEFA, CK-MB, L-lactate, glucose, insulin, and cortisol were higher at M1 and the RQUICKI and RQUICKI-βHB indices were lower at this moment. L-lactate, CK, and CK-MB were higher in the RDA group, while cTnI, βHB, and LDH did not present a group or moment effect. Cardiac markers correlated with the energy profile metabolites, L-lactate, and cortisol. Discussion: The high concentrations of NEFA at M1 reflected the condition of negative energy balance. βHB concentrations were stable, that may be related to the number of days postpartum in which the animals were diagnosed. The hyperglycemic condition and the increase in serum cortisol concentrations found at M1 can be induced by the condition of metabolic stress resulting from the disease. Hyperinsulinemia were recorded in the present study could be an important factor related to the pathogenesis of DA, since there seems to be a correlation between hyperinsulinemia and decreased abomasal emptying rate. The RQUICKI and RQUICKI-βHB indices was significantly lower at M1, which may indicate lower sensitivity of peripheral tissues to insulin at this time. Changes in serum activity of LDH and CK may result from tissue damage due to organ displacement, in addition to damage associated with surgery and the administration of injectable drugs, mainly intramuscularly. The elevation in plasma L-lactate at M1 and in the RDA group may be associated with abomasal hypoperfusion. The high positive correlations found between L-lactate and the variables glucose, insulin, and cortisol reinforcing the association between the concentration of L-lactate and the moment of greatest stress. The increase in cardiac biomarkers may be related to the occurrence of ischemia/reperfusion injury in the abomasum, which involves oxidative stress and the production of inflammatory mediators. The hyperglycemic condition and the higher concentrations of NEFA can also contribute to the occurrence of myocardial injury. The correlations found between cardiac biomarkers and plasma L-lactate, strengthen the idea that there is a relationship between L-lactate and myocardial injury. In this sense, the measurement of blood concentrations of cTnI, CK-MB, and L-lactate could contribute as severity markers and prognosis indicators in cattle with DA.